Social Commerce Success Impact on Business Performance Insight From TikTok Shop Phenomena in Indonesia - Ardiansah, Muhammad Noor; Azizah, Asmaul; Sadida, Afiat (Universitas Negeri Semarang, 2024)
Purpose : Social commerce has revolutionized as a more interactive business platform beyond e-commerce, but there are still limited studies on its success and impact on TikTok Shop’s performance case as the most popular social commerce. This study investigates the determinants of success in the framework of Delone and Mclean’s information system success model, which was developed by attributing its impact on TikTok Shop’s business performance.Method : The research was conducted on Generation Z users and entrepreneurs who use TikTok Shop as an essential part of business in Indonesia, using SEM analysis through the stages of outer model, inner model, goodness fit, and hypothesis testing.Findings : The results show that the usage level is indicated by system quality and trust, while user satisfaction is indicated by information quality, service quality, and trust, which affect the success of TikTok Shop and positively influence the seller’s business performance. Social media transformation into social commerce requires consideration of usage and user satisfaction as determinants of system success that practically affect the seller’s business performance. Novelty : The study proposes the trust variable as an extension of Delone and Mclean’s ISSM and examines its direct relationship with multidimensional seller performance so that it can be developed to enrich the existing model.